2018
DOI: 10.3389/fvets.2018.00251
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Appraisal of Probiotics for Mastitis Control

Abstract: The urge to reduce antimicrobials use in dairy farming has prompted a search for alternative solutions. As infections of the mammary gland is a major reason for antibiotic administration to dairy ruminants, mammary probiotics have recently been presented as a possible alternative for the treatment of mastitis. To assess the validity of this proposal, we performed a general appraisal of the knowledge related to probiotics for mammary health by examining their potential modes of action and assessing the compatib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 111 publications
(145 reference statements)
1
53
0
Order By: Relevance
“…The results showed that probiotics could be a natural and effective alternative in the prevention of bovine mastitis at dryoff period and act as an immunomodulator stimulating local and systemic defense lines (Pellegrino et al, 2017). On the other hand, other studies suggest that intramammary probiotics should be considered with caution, although teat apex probiotics deserve further research (Rainard and Foucras, 2018). Clearly, more research is needed for understanding the impact of administration of probiotics on the cow milk microbiota as well as on the offspring gastrointestinal microbiota and on their respective health status.…”
Section: Can We Manipulate the Milk Microbiota In Order To Improve Mamentioning
confidence: 97%
“…The results showed that probiotics could be a natural and effective alternative in the prevention of bovine mastitis at dryoff period and act as an immunomodulator stimulating local and systemic defense lines (Pellegrino et al, 2017). On the other hand, other studies suggest that intramammary probiotics should be considered with caution, although teat apex probiotics deserve further research (Rainard and Foucras, 2018). Clearly, more research is needed for understanding the impact of administration of probiotics on the cow milk microbiota as well as on the offspring gastrointestinal microbiota and on their respective health status.…”
Section: Can We Manipulate the Milk Microbiota In Order To Improve Mamentioning
confidence: 97%
“…It is possible that the presence of the LACT organisms inhibited the development of any teat skin or mammary gland dysbiosis. The use of probiotics to minimize the risk of (or correct existing) dysbiosis has been proposed as a method to both reduce mastitis risk and the need for antimicrobial use (29). An additional potential protective effect may be the result of barrier-like biofilm properties of the organisms (20).…”
Section: Discussionmentioning
confidence: 99%
“…The use of these products has occasionally raised concerns about the risk of chemical residues in milk (26)(27)(28). Lactic acid bacteria (LAB) are part of the healthy alimentary microbiota (29), and have been proposed as a potential alternative therapy for the control of bovine mastitis (30,31). A liquid product containing a mixture of Lactobacillus organisms (LACT) was developed as a post-milking teat spray.…”
Section: Introductionmentioning
confidence: 99%
“…The probiotic interaction with host's system microbiota (e.g. udder, rumen, intestine) results in correcting system dysbiosis 9 and controlling several infectious inflammatory conditions through antagonism and immunomodulation 10 . Lactic acid bacteria (LAB) that are well known antibacterial producers and generally recognised as safe in the food industry offer a possible alternative to conventional antimicrobials 11 .…”
mentioning
confidence: 99%
“…A dysbiosis of the commensal intramammary microbiota and the presence of mastitis causing-bacteria has been linked to IMI in dairy cattle 12 . The use of probiotics is proposed to correct the dysbiosis 9 .…”
mentioning
confidence: 99%